The role of innovative technologies in efficiency increase of agriculture - S. A. Raeva (Зерновое хозяйство России, 2019)
The introduction of new technologies is a key factor in the competitiveness of agriculture. The use of innovative technologies provides an increase in profitability, efficiency and sustainability of agricultural production. This is achieved by economizing of fertilizers, protective remedies, growth regulators, seeds, fuel; by reducing labor costs and increasing soil fertility. Innovations should become an integral part of the investments aimed at strengthening the material and technical base of enterprises. The prohibition of agricultural product imports contributed to the improvement of the financial situation of agricultural enterprises, which allows agricultural producers to introduce innovations.